Anti‐EF‐Tu IgG titers increase with age and may contribute to protection against the respiratory pathogen Haemophilus influenzae. Issue 3 (3rd January 2019) - Thofte, Oskar; Kaur, Ravinder; Su, Yu‐Ching; Brant, Marta; Rudin, Anna; Hood, Derek; Riesbeck, Kristian
Abstract: Non‐typeable Haemophilus influenzae (NTHi) is a pathogen that commonly colonizes the nasopharynx of preschool children, causing opportunistic infections including acute otitis media (AOM). Patients suffering from chronic obstructive pulmonary disease (COPD) are persistently colonized with NTHi and occasionally suffer from exacerbations by the bacterium leading to increased morbidity. Elongation‐factor thermo unstable (EF‐Tu), a protein critical for bacterial protein synthesis, has been found to moonlight on the surface of several bacteria. Here, we show that antibodies against NTHi EF‐Tu were present in children already at 18 months of age, and that the IgG antibody titers increased with age. Children harboring NTHi in the nasopharynx also displayed significantly higher IgG concentrations. Interestingly, children suffering from AOM had significantly higher anti‐EF‐Tu IgG levels when NTHi was the causative agent. Human sera recognized mainly the central and C‐terminal part of the EF‐Tu molecule and peptide‐based epitope mapping confirmed similar binding patterns for sera from humans and immunized mice. Immunization of BALB/c and otitis‐prone Junbo (C3H/HeH) mice promoted lower infection rates in the nasopharynx and middle ear, respectively. In conclusion, our results suggest that IgG directed against NTHi EF‐Tu may play an important role in the host immune response against NTHi. Abstract : Increased concentrations of IgG directed against non‐typeable Haemophilus influenzae (NTHi) elongation‐factor thermo unstable (EF‐Tu) are found in adults compared to toddlers. In children with acute otitis media, anti‐EF‐Tu IgG is correlated to NTHi colonization in the nasopharynx. Finally, mice immunized with recombinant EF‐Tu are partially protected from NTHi colonization and otitis media.